Cross-Cultural Transference in Translation: Translator Preferences in Translating Cultural Elements from Turkish to English in Madonna in a Fur Coat By Sabahattin Ali - DEMİREL, Hakan Hilmi; İŞİSAĞ, Korkut Uluç (International Journal of Educational Technology and Learning, 2019)
This study aims at examining the translation process of culture specific items (CSI) in Sabahattin Ali’s Kürk Mantolu Madonna (1943) and English translation entitled Madonna in a Fur Coat (2016) in a descriptive manner. To achieve this primary aim, the researchers have classified the cultural elements in the source text according to Aixelá’s (1996) ‘Categorization of Culture-specific Items’ and analyzed the samples according to the taxonomies proposed by Franco Aixelá's (1996) for the translation of culture-specific items. In order to set a general framework, the analysis has focused upon the answers of the questions that; which procedures and strategies are used by the translators in the process of transferring the culture-specific items from the source language into the target language; which translation procedures of Javier Aixelá’s are used more or less frequently by the translators; and which one of the translation strategies suggested by Venuti is generally referred to by these strategies; either domestication or foreignization. Besides, to what extent the otherness of Turkish culture has been recreated in the English translation of Kürk Mantolu Madonna according to the dominance of either of these strategies has also been clarified. Consequently, the general approach of the translators who have transferred the novella into the target language will be detected by the researchers. Likewise, a number of translation strategies necessary to deal with the translation of CSIs have also been illustrated; and also some categorization types of those CSIs to be employed during the classification process of cultural elements in the literary texts have been presented.